IMPLEMENTATION OF SCHOOL VIOLENCE PREVENTION AND HANDLING IN PURWAKARTA - Aisah Jamil, Nur; Yulianty S, Nadya (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study discusses the implementation of violence prevention and handling in the context of educational psychology in educational units. This study explores psychological strategies that can be applied to address violence in schools, as well as their impact on the learning environment. In addition, this study analyzes approaches to violence prevention and effective coping mechanisms, with the aim of improving students' psychological well-being and creating a safe and supportive learning environment. This study uses a descriptive qualitative research method. This descriptive qualitative study explains and depicts facts or circumstances that occur in the socialization process carried out by the KPAI of Purwakarta City. The researcher describes and elaborates on the implementation of socialization activities for the Prevention and Handling of Bullying Violence in Educational Units in Purwakarta. The findings show that socialization of prevention and handling of bullying violence in educational units can reduce incidents of violence and improve the quality of the overall educational experience. Prevention in educational units can be carried out by the school by imposing strict sanctions if there are actions that are detrimental to many parties, in order to minimize actions that have a negative impact on both students and the school. Parents are also expected to provide more affection to their children so that they become more productive in doing various things. Government support in this regard is expected to pay more attention to remote schools, far from city centers that sometimes have more obstacles in preventing and dealing with students who have committed acts of violence, which sometimes cannot be resolved by teachers and authorized institutions.